PERKENALAN DENGAN ALIRAN FILSAFAT PENDIDIDKAN - Mansur, Rosichin (Thufuli, 2020)
The schools of educational philosophy believe in their views for development and change. The flow of philosophy makes the world of education more advanced and quality. The views of progressivism, perennialism, essentialism, constructionism andconstructivism are projected in educators, students, curriculum, principles of education and learning. Early Childhood Islamic Education (PIAUD) is one of the media for actualizing the views of educational philosophical schools that are relevantto local culture. so that many schools of philosophy can be adopted.